Insights Into an Unexplored Component of the Mosquito Repeatome: Distribution and Variability of Viral Sequences Integrated Into the Genome of the Arboviral Vector Aedes albopictus - Pischedda, Elisa; Scolari, Francesca; Valerio, Federica; Carballar-Lejarazú, Rebeca; Catapano, Paolo Luigi; Waterhouse, Robert M.; Bonizzoni, Mariangela (Frontiers in Genetics, 2019)
The Asian tiger mosquito Aedes albopictus is an invasive mosquito and a competent vector for public-health relevant arboviruses such as Chikungunya (Alphavirus), Dengue and Zika (Flavivirus) viruses. Unexpectedly, the sequencing of the genome of this mosquito revealed an unusually high number of integrated sequences with similarities to nonretroviral RNA viruses of the Flavivirus and Rhabdovirus genera. These Nonretroviral Integrated RNA Virus Sequences (NIRVS) are enriched in piRNA clusters and coding sequences and have been proposed to constitute novel mosquito immune factors. However, given the abundance of NIRVS and their variable viral origin, their relative biological roles remain unexplored. Here we used an analytical approach that intersects computational, evolutionary and molecular methods to study the genomic landscape of mosquito NIRVS. We demonstrate that NIRVS are differentially distributed across mosquito genomes, with a core set of seemingly the oldest integrations with similarity to Rhabdoviruses. Additionally, we compare the polymorphisms of NIRVS with respect to that of fast and slow-evolving genes within the Ae. albopictus genome. Overall, NIRVS appear to be less polymorphic than slow-evolving genes, with differences depending on whether they occur in intergenic regions or in piRNA clusters. Finally, two NIRVS that map within the coding sequences of genes annotated as Rhabdovirus RNA-dependent RNA polymerase and the nucleocapsid-encoding gene, respectively, are highly polymorphic and are expressed, suggesting exaptation possibly to enhance the mosquito’s antiviral responses. These results greatly advance our understanding of the complexity of the mosquito repeatome and the biology of viral integrations in mosquito genomes.